Editorial - Pawlak, Mirosław (Studies in Second Language Learning and Teaching, 2020)
It is with great pleasure that I am sharing with you this new issue of Studies in Second Language Learning and Teaching. Since the first issue in 2020 was a special issue guest-edited by Laura Gurzynski-Weiss, I did not have the chance to emphasize the fact that the journal has entered its tenth year of existence. These ten years have passed very quickly and the journey we have travelled is truly exceptional. When we were putting together the first issues, it was so hard to find good papers and we had to continually struggle trying to convince our colleagues that SSLLT had much potential and was the right choice for publishing their work. At present, we are receiving several hundred submissions per year and the rejection rate by far exceeds 80%. At the same time, an increasing number of submissions represent outstanding scholarship, with the effect that the papers that ultimately get accepted and published are also getting better and better. I would like to take this opportunity to express my gratitude to all those who have supported SSLLT from the get-go – the co-editors, the members of the Editorial Board, the reviewers, the guest-editors of special issues and all the contributors. I will have much more to say about this special anniversary in the December edition where I will also be announcing the way in which we are planning to celebrate it.